Diagnostic role of cone beam computed tomography for the position of straight array. (3rd April 2018) - An, Seo-Young; An, Chang-Hyeon; Lee, Kyu-Yup; Jang, Jeong Hun; Choung, Yun-Hoon; Lee, Sang Heun
Abstract: Objective: To assess the usefulness of cone beam computed tomography (CBCT) for characterizing electrode insertion and evaluate the influence of electrode insertion status on post-cochlear implantation (CI) outcomes. Design: Twenty-six ears with post-CI CBCT scans were included. The devices were MED-EL Flex28 ( n = 21) and Nucleus slim straight ( n = 5). The parameters including cochlear duct length (CDL), insertion depth angle (IDA), insertion length of electrode (IL), and cochlear coverage (CC) were analyzed and compared with aided pure-tone threshold (PTA) with implant in free field, and open-set sentence score. Results: The mean CDL was 36.8 ± 1.4 mm. Electrode array was dislocated into scala tympani in two ears. The mean IL and IDA were 26.5 ± 1.9 mm and 541.4 ± 70.2°. The mean linear CC (IL/CDL, 0.73 ± 0.06) was larger than the mean angular CC (IDA/900, 0.60 ± 0.08). The CBCT parameters showed correlation one another. While the aided pure-tone threshold was correlated with IL and IDA, there were no significant correlations in the open-set sentence score. For the postlingually deaf patients with single electrode (Flex 28), the sentence score had no significant correlation and the aided PTA was positively correlated with IL ( R = 0.517, p = .028). Conclusions: This study validated the CBCT evaluating the electrode array position. The CBCT could be helpful for the preoperative selection of the optimal array and prediction of the CC.